Pengaruh Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Pada GIGG Store Samarinda - Sarwo Eddy Wibowo 3, Sufiandi1 Eddy Soegiarto2 (EKONOMIA, 2021)
The Influence Of Product Quality And Brand Image On Purchase DecisionÂ  GIGG Store Samarinda. Eddy Soegiarto and Sarwo Eddy Wibowo.This study discusses product quality and price variables on purchasing decisions at Samarinda GIGG Store. With a sample of 96 respondents obtained using the simple random sampling method. Meanwhile, the collecting data is carried out by using an online questionnaire that has purchased GIGG Store Samarinda productsAnalysis tools and hypothesis testing in this study is by using multiple linear regression analysis tools, partial test (t test), simultaneous test (f test), multiple correlation analysis (R), coefficient of determination (R2), Correlation Coefficient (r).Â  Based on data analysis, the results of this study indicate that product quality and brand image variables together have a positive and significant effect on purchasing decisions. R value of 0.624 or 62.4%, this means that overall product quality variables and brand image have a strong relationship to the purchase decision variable. The coefficient of determination (R2) of 0.376 or 37.6% shows that the quality of the product and brand image can explain the variations that occur in purchasing decisions at Samarinda GIGG Store. Correlation Coefficient (r) all variables have a significant relationship seen from the significance value of 0,000> 0.05From the simultaneous test results (test f) the value of Fcount> Ftable (29.62> 4.84), this shows that the product quality and brand image variables simultaneously have a positive and significant effect on Purchasing Decisions. Partial test results (t test) indicate that product quality has a positive and significant effect on purchasing decisions seen from the value of sig. 0.012 <0.05, then the brand image variable has a positive and significant influence on purchasing decisions seen from the sig value. At 0.004 <0.05.